SYSTEMATIC LITERATURE REVIEW APPLICATION OF METHODS IN INFORMATION SYSTEMS DEVELOPMENT - Gita Cahyani, Annisa Putri; Mahdiana, Deni (Informatika, Universitas Jenderal Soedirman, 2024)
In today's rapidly changing digital age, information system development is critical to the growth and success of organizations and businesses. It is critical to select the appropriate system development method because it can impact many aspects of the system, including efficiency, dependability, and alignment with organizational requirements. Businesses or organizations may struggle to determine the best approach based on their project environment and specific requirements. The goal of this study is to gain a better understanding of the various approaches to systems development and how they work. In information systems, each system development technique's complexity and effectiveness will be investigated using a qualitative approach in conjunction with descriptive analysis. A better understanding of the features and benefits of each method, such as agile, waterfall, Rapid Application Development (RAD) and others, will be enable organizations to make more precise and goal-driven decisions. Furthermore, this study will look at previous research on a variety of topics and discussions, such as information system design and the practical application of cutting-edge software. Determine trends, best practices, and issues that have emerged during the development of current information systems. One of the motivations for this research is the growing complexity of project environments, as well as the need for dependable and efficient systems. Learning more about systems development techniques can assist organizations and businesses in lowering project risks, increasing efficiency, and identifying solutions that better meet their business goals. The waterfall method is most popular because it provides more control over the system development process.